Symmetric aqueous rechargeable lithium battery using Na1.16V3O8 nanobelts electrodes for safe high volume energy storage applications - Nair, Vivek Sahadevan (2014)
Synthesis of bundled, single crystalline Na1.16V3O8 nanobelts is done by a simple and novel cost-effective low-temperature hydrothermal method and further annealed at different temperatures. These nanobelts are applied as both cathode and anode material for aqueous rechargeable lithium ion battery. The morphologies and structure of Na1.16V3O8 nanobelts are studied via field-emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) and X-ray diffraction (XRD) techniques. The nanobelts are observed to have a large aspect ratio, with a diameter of 75(±5)nm and an average length of ∼5 μm. Electrochemical behavior of Na1.16V3O8 nanobelts were studied via cyclic voltammetry (CV) and galvanostatic studies. Systematic, comparative studies for Na1.16V3O8 annealed at various temperatures showed a good reversible initial discharge capacity values, with a maximum of high-temperature-annealed symmetric Na1.16V3O8 cell has an initial discharge capacity of ∼152.42 mAhg−1 and >75% retention of initial capacity over 100 charge/discharge cycles exhibiting excellent cyclic stability and rate performance at a current density of 5000 mAg−1. The pseudocapacitive surface charging in Na1.16V3O8 nanobelts which facilitate low energy Li+ pathways from surface to the subsurface V3O8− interlayer sites could be the main reason for its high rate performance capabilities observed.